PENDAMPINGAN PEMERINTAHAN GAMPONG DALAM MENINGKATKAN TATA KELOLA ADMINISTRASI DESA (BEST PRACTICE DI GAMPONG TEUNGOH BARO) - Fanzikri, Mirza (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2022)
Abstract: Gampong Teungoh Baroh Kecamatan Peukan Baro Kabupaten Pidie is a locus that requires strengthening and improving village administration governance by the mandate of the Minister of Home Affairs regulation on Number 47 of 2016 concerning Village Government Administration. This study explains efforts to assist village administration in Gampong Teungoh Baroh Kecamatan Peukan Baro Kabupaten Pidie. This research was carried out in conjunction with community service using the Participatory Learning and Action (PLA) method, a participatory learning and practice process which positions the target of coaching and the subject of implementing village administration. This activity is designed in two dimensions. The research dimension uses data collection techniques through observation, interviews, document review, and the coaching dimension, which consists of several activities. Participants who were targeted and informants in this community service consisted of elements of Keuchik, Gampong Apparatus, TPG, and village cadres. Data analysis in this study uses data collection techniques, reduction, simplification, and conclusion. The results of the study describe the stages of assistance in four functions. Namely, the function of; empowering, protecting, supporting and facilitating. Assistance activities for village administration governance were held in the form; of socialisation for the regulation of Minister of Home Affairs Number 47 of 2016, workshops for filling out village administration register books, supervision and consultation on village administration.Keywords: Village Administrations; Village Assistance; Community Service.Abstrak: Gampong Teungoh Baroh Kecamatan Peukan Baro Kabupaten Pidie merupakan lokus yang membutuhkan penguatan dan peningkatan tata kelola administrasi pemerintahan desa. Di sana ditemukan bahwa belum tersedianya buku register administrasi desa sesuai dengan amanat Permendagri Nomor 47 tahun 2016 Tentang Administrasi Pemerintahan Desa. Penelitian ini memberikan penjelasan terkait upaya pendampingan tata kelola administrasi desa di Gampong Teungoh Baroh Kecamatan Peukan Baro Kabupaten Pidie. Penelitian yang dilaksanakan bersamaan dengan pengabdian masyarakat ini menggunakan metode Participatory learning and Action (PLA) atau proses belajar dan praktik secara partisipatif, yang memposisikan sasaran pembinaan juga sebagai subjek pelaksana administrasi desa. Kegiatan ini didesain dalam dua dimensi. Dimensi penelitian menggunakan teknik pengumpulan data secara observasi, wawancara, dan telaah dokumen serta dimensi pembinaan yang terdiri dari beberapa kegiatan. Peserta yang menjadi sasaran merangkap informan dalam pengabdian masyarakat ini terdiri dari unsur Keuchik, Aparatur Gampong, TPG, dan para kader LKD Gampong Teungoh Baroh. Analisis data dalam penelitian ini menggunakan teknik pengumpulan data, reduksi, penyederhanaan, dan penarikan kesimpulan. Hasil penelitian menguraikan tahapan pendampingan dalam empat fungsi, yaitu fungsi penguatan (empowering), perlindungan (protecting), pendukungan (supporting), dan fasilitasi (facilitation). Kegiatan pendampingan tata kelola administrasi desa diselenggarakan berupa sosialisasi Permendagri Nomor 47 tahun 2016, lokakarya (workshop) pengisian buku register administrasi desa, serta supervisi dan konsultasi penyelenggaraan administrasi pemerintahan desa.Kata Kunci: Administrasi Desa; Pendampingan Desa; Pengabdian Masyarakat.